Accelerating socio-economic justice through inclusive economic-and-employment growth - Isaacs, Nandipha (University of the Witswatersrand, Johannesburg, 2023)
This paper posits that the labour market, through paying jobs, is an important lever for moving people out of poverty to address the social and economic consequences of apartheid in South Africa. The paper explores different parameters related to employment growth, namely the relationship between economic growth and employment growth, which types of business (small versus large) contribute most to employment growth, which sectors contribute most to employment growth, the barriers to employment growth experienced by entrepreneurs, and interventions required to ensure employment growth is inclusive. This research applied the ARDL model to understand the relationship between employment growth and economic growth on an aggregate level, at a sector level and a business size level, using StatsSA and SARB data for the period 2009 - 2019. This was supplemented by interviews with entrepreneurs and subject matter advisors who provided additional insights into the dynamics of employment growth. The findings of the report highlight that there is a positive relationship between economic growth and employment growth in South Africa, confirming that economic growth has contributed positively to the labour market, despite high and rising unemployment. Key sectors also show a positive relationship with economic growth. The findings revealed as well that small business employment has a negative relationship with economic growth. This paper also highlights that indicators that are affected by apartheid are still used in recruitment and promotion decisions, pointing to the need for company practices and policies to be re-looked to ensure Black Africans are not locked out of the economy.
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Management (in the field of Public Policy) at the Wits School of Governance
Keywords: Employment growth; economic growth; SMMEs; Inclusive growth; South Africa; UCTD; SDG-8: Decent work and economic growth